Nepotisme dalam Pemerintahan Desa: Studi Kasus Penyelenggaraan Pemerintahan di Kabupaten Kuantan Singingi Tahun 2015-2021 - Kaffah, Fhisilmi; Desbanita, Irda; Hafizah, Aini; Adlin, Adlin (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
The practice of nepotism has colored the governance of Serosah Village for the 2015-2021 period. Nepotism is carried out when there is a recruitment and selection process for a position. Nepotism has two perspectives, namely from the perspective of the form of relationship (Kinshipism, Familism, Clanism, Patriotism, Racism, Sexism, Planetism) and from an ethical perspective (Favoritism, Discrimination, Partial Justice. Merit system). The research method used in this research is qualitative research. The type of research is descriptive qualitative research. The research location is in Serosah Village, Hulu Kuantan District, Kuantan Singingi Regency. The results of the research carried out were that the Head of Serosah Village committed acts of nepotism in the administration of village government, namely in the management of BUMDES, PAUD, MDA, youth organizations and SPSI. The practice of nepotism is carried out due to factors of familism (relationship perspective) and favoritism (ethical perspective). The Serosah Village Head gives positions to children, family (familism) and people close to him (favouritism) and controls the political and economic resources in Serosah Village to gain personal benefit. The recruitment and selection process for positions is based on aspects of heredity and those who are in her favor.